2020
DOI: 10.4209/aaqr.2019.12.0656
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Silica, Arsenic, and Chromium (VI) in Cement Workers: A Probability Health Risk Assessment

Abstract: Cement mineral dust contains a variety of carcinogenic and non-carcinogenic substances. The study aimed to determine the probability of health risk among cement workers due to respirable silica (Si), arsenic (As), and chromium (Cr) VI dust exposure. A cross-sectional study was carried out among 123 cement workers. A personal air sampling pump was used to assess respirable cement dust exposure. Inductively coupled plasma mass spectrometry (ICP-MS) was used for As, and Cr analysis, and X-ray powder diffraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…We found that concentrations of arsenic, barium, and zirconium were significantly higher in the CPM (762.4, 1696.0, and 51.2 ppb, respectively) compared with the PM used in the previous study (20.67, 90.80, and 30.05 ppb, respectively) [30] , and thallium was detected at a significant level in the current sample. Inhaled arsenic was closely associated with a high cancer risk among cement workers, as were silica and hexavalent chromium [20] . In addition, thallium can bind to particles during coal combustion and cement production [22] , barium and zirconium have also been known to be applied in some cement manufacturing processes to improve the quality of concrete [1] , [50] .…”
Section: Discussionmentioning
confidence: 98%
“…We found that concentrations of arsenic, barium, and zirconium were significantly higher in the CPM (762.4, 1696.0, and 51.2 ppb, respectively) compared with the PM used in the previous study (20.67, 90.80, and 30.05 ppb, respectively) [30] , and thallium was detected at a significant level in the current sample. Inhaled arsenic was closely associated with a high cancer risk among cement workers, as were silica and hexavalent chromium [20] . In addition, thallium can bind to particles during coal combustion and cement production [22] , barium and zirconium have also been known to be applied in some cement manufacturing processes to improve the quality of concrete [1] , [50] .…”
Section: Discussionmentioning
confidence: 98%
“…The management of such chronic diseases may become burdensome and often impossible for the working class who are living in poverty, particularly in LMICs [29,55]. Subclinical inflammation under cement dust exposure may be determined using RDW and MCV, which are sensitive to early inflammatory changes and are accessible and affordable [30,[56][57][58].…”
Section: Problem Statementmentioning
confidence: 99%
“…Additionally, no toxicity tests were conducted on cement dust such as the Microtox bioassay. The primary carcinogenic elements in cement dust are As, silica (Si), and chromium (Cr) [79]. A study by Kamaludin et al [79] addressed the toxic effects of exposure to As-, Si-, and Cr-rich cement dust for cement workers and administrative staff in the cement industry.…”
Section: Physical and Chemicalmentioning
confidence: 99%
“…The primary carcinogenic elements in cement dust are As, silica (Si), and chromium (Cr) [79]. A study by Kamaludin et al [79] addressed the toxic effects of exposure to As-, Si-, and Cr-rich cement dust for cement workers and administrative staff in the cement industry. Administrative staff had higher risk of exposure and health impacts such as lung damage because of the absence of control measures (e.g., N95 masks) [79].…”
Section: Physical and Chemicalmentioning
confidence: 99%